GOVERNMENTAL AND MANAGERIAL FACTORS HAMPERING THE GROWTH OF SMALL SCALE ENETERPRISES IN ENUGU, NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The persistent failure of small scale businesses in Nigeria is alarming and needs timelyintervention particularly in Enugu State. This, however, informed the present study to determinegovernmental and managerial factors hampering the growth of small scale enterprises in EnuguState. Two purpose statements, two research questions and four hypotheses guided the study.The research design was descriptive survey. Simple random technique was used to select 120registered entrepreneurs for the study. The instrument for data collection was a structuredquestionnaire. The questionnaire was tested for validity and reliability. Using Cronbach’salpha, the overall reliability coefficient was 0.82. Descriptive statistics of mean and standarddeviation were used to answer the research questions. The t-test for non-correlated data wasused to test the hypotheses at 0.05 level of significance. Findings from the study revealed amongothers that governmental and managerial factors hamper the growth of small scale enterprisesin Enugu State. The findings revealed that the respondents differ significantly in their meanratings on governmental and managerial factors that hamper the growth of SSEs based onlocation. Similarly, the findings revealed that the respondents do not differ significantly in theirmean rating on governmental factor that hamper the growth of SSEs in Enugu State based onlocation. However, the respondents differed significantly in their mean rating on governmentalfactor that hamper the growth of SSEs based on years of experience. Similarly, the respondentsdo not differ significantly in their mean rating on managerial factor that hamper the growth ofSSEs in Enugu State based on years of experience. Based on the findings, it was recommendedamong others that Enugu state should be consistent in her policies and regulations with regardsto the affairs of small scale enterprises. Entrepreneurs in Enugu State should strive to employcompetent managers to their enterprises as that will enhance enterprise growth anddevelopment among others.